Students Perceptions of Biology Learning in the Implementation of the Merdeka Curriculum - Suwandi, Dhian Permata; Afandi, Afandi; Tenriawaru, Andi Besse (Jurnal Pijar Mipa, 2024)
The Merdeka Curriculum is being implemented after several curriculum changes in Indonesia. The Indonesian government has adjusted the curriculum as much as possible to meet the expected educational objectives. Merdeka Curriculum is a curriculum centred on a learner interest and talent approach. The Merdeka Curriculum seeks to form resilient, independent, and creative learners through a more open and inclusive approach. This study analyses students' perceptions of biology learning in implementing the Merdeka Curriculum at MAN 2 Pontianak. This research uses a descriptive method with a qualitative approach. This research was conducted in July 2024 at MAN 2 Pontianak, South Pontianak District, Pontianak City. The sample used in this study amounted to 140 students in the biology interest class. The data collection technique in this study used a survey with a questionnaire instrument. The questionnaire consists of 38 statements. Based on the results of data processing and analysis of the research data that has been described, it is found that the average of all indicators on the independent curriculum variable is 77% good category, then on the cognitive understanding variable, the average of all indicators is 71% good category. On the Pancasila student profile variable, the average of all indicators is 80% good category. Based on the overall results of the recapitulation of all indicators of students' perceptions of biology learning at MAN 2 Pontianak, the average is 76% in the good category. Thus, students can implement the independent curriculum at MAN 2 Pontianak well. This indicates that the independent curriculum can encourage adequate cognitive understanding, strengthen the values of the Pancasila learner profile, and create compelling learning experiences. Therefore, this curriculum can be a solid foundation for continuously improving the quality of learning at MAN 2 Pontianak.